2004
DOI: 10.14314/polimery.2004.283
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of smoke emission properties of plastics

Abstract: Pod.ŻJs poż óti oPró., PIońicnj, obffuqe 5iq $-vdziclanic zoJcznych dij d]rń! ' k tóly njejĆd n Óklot ruc zwiękzi lĘb. oliał lEldńia Pbwad?nic ar.]i n zfunć' os,bv ńając bczPośrcdni *onhkt z zagrożcń olienta.ię wPomilsz.zeniid! wPidają r' pJn]kc, i hkrą.yĆh r'yci! PodĆzas lozFrz.$lzcliaja..go sig poż l W ie!ńinologii ńzyczn.]dyń dĆIŃiujĆ sĘ FkÓ &mzo]' W którym gaz stanowi 'azq rozF€ sŻaiiĆą, mtonj3$ cńlo śale lub .iez jcl lazi rozlro lex (l) miesz.zą sig w PŹ.dziaie 1o |r |' \Ą' nÓmĆnklafurzĆ Poźarni.zej uż),!… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Burning of polymers and polymeric materials is accompanied by smoke formation. Restricting the smoke formation is an important problem when studying the fl ammability of polymers [10][11][12]. We found that curing the rubbers with iodoform did not appreciably increase their smoke formation (determined by the average mass optical density) when compared with the deterioration of this property in the case of vulcanisates cured with peroxide or sulphur ( Table 2).…”
Section: Flammability Assessed Using the Cone Calorimetermentioning
confidence: 89%
“…Burning of polymers and polymeric materials is accompanied by smoke formation. Restricting the smoke formation is an important problem when studying the fl ammability of polymers [10][11][12]. We found that curing the rubbers with iodoform did not appreciably increase their smoke formation (determined by the average mass optical density) when compared with the deterioration of this property in the case of vulcanisates cured with peroxide or sulphur ( Table 2).…”
Section: Flammability Assessed Using the Cone Calorimetermentioning
confidence: 89%
“…Procesom spalania polimerów i materia³ów polimerowych towarzyszy wydzielanie siê dymu. Ograniczenie dymotwórczooeci stanowi istotny problem zwi¹zany z zagadnieniem palnooeci polimerów [10][11][12]. Stwierdzilioemy, ¿e usieciowanie badanych kauczuków jodoformem nie wp³ynê³o w istotnym stopniu na zwiêkszenie ich dymotwórczooeci (okreoelonej oeredni¹ masow¹ gêstooe-ci¹ optyczn¹ dymu) w porównaniu z pogorszeniem tej Fig.…”
Section: Palnooeae Oceniana Za Pomoc¹ Kalorymetru Sto¿kowegounclassified
“…Modyfikacja epoksydów zwi¹zkami halogenowymi, g³ównie bromowymi, jest nadal przedmiotem badañ wielu ooerodków naukowych na oewiecie [8,9]. Niestety podczas spalania tego typu produktów wydzielaj¹ siê do oerodowiska truj¹ce gazy, czêsto stanowi¹ce wiêksze zagro¿enie ni¿ sam ogieñ [10]. Dlatego ten kierunek modyfikacji podlega ostrej krytyce i coraz czêoeciej pojawiaj¹ siê opracowania i raporty dotycz¹ce ograniczenia produkcji i zu¿ycia bromopochodnych oerodków uniepal-niaj¹cych oraz korzyoeci z zast¹pienia ich bezhalogenowymi antypirenami [11], g³ównie zwi¹zkami tlenków i wodorotlenków metali.…”
Section: Problemy Uniepalniania¯ywic Epoksydowych -Obecny Stan Wiedzȳunclassified